Analisis Efektivitas Tehnik Relaksasi Progresif Terhadap Nyeri Luka Episiotomi Pada Ibu Post Partum di RSUD Genteng Banyuwangi - Rahmawati Raharjo; Ayuk Naimah; Rini Setyawati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Postpartum pain experienced by every woman has varying degrees of pain with different pain thresholds. Post partum pain is caused by a tear in the birth canal / perineum due to an episiotomy with the aim of preventing spontaneous perineal tearing and facilitating delivery. The research method used is experimental research with pre-experimental design research techniques. Experimental research method is a research method carried out to find the effect of certain treatments under controlled conditions. The research variables consisted of the independent variable (progressive relaxation technique) and the dependent variable (episiotomy wound pain). The population was 35 respondents with episiotomy wounds at the Genteng Regional Hospital Banyuwangi. The sampling method in this study used a total sampling technique so that the sample used was 35 respondents. The instrument in this study used MC Gill's observation sheet with the aim of assessing pain response in mothers with episiotomy wounds. The analytical test used is the Wilcoxone test (sig value <0.05 then Ha is accepted) and is used as an alternative to the Paired Sample T Test if the data is not normally distributed. From the results of the study, it was concluded that there was a difference in pain scale between the pre test and post test (sig value 0.000, where the sig value was 0.000 <0.05). Progression relaxation has a positive impact on quality of life which includes multiple dimensions such as increased sleep quantity and quality, decreased physical restrictions, mothers will be more independent in carrying out activities, social relationships, sexual life can take place according to the postpartum phase Keywords: Episiotomy pain, Post partum, Progressive relaxation